RETRACTED: The Novel Tumor Suppressor Gene ZNF24 Induces THCA Cells Senescence by Regulating Wnt Signaling Pathway, Resulting in Inhibition of THCA Tumorigenesis and Invasion - Xiong, Juan; Jiang, Panpan; Zhong, Li; Wang, Youling (Frontiers in Oncology, 2021)
Object：Clinically, the effective treatment options available to Thyroid cancer (THCA) patients are very limited. Elucidating the features of tumor suppressor genes (TSGs) and their signaling cascade may provide clues for the development of new strategies for targeted therapy of THCA. Therefore, this paper aims to investigate the molecular mechanism of ZNF24 underlying promoting THCA cell senescence. Methods: We performed RT-PCR and Western Blot assays to evaluate the expression levels of associated RNA and protein. The proliferation, migration and invasion of THCA cells were examined by CCK8 assay, Colony forming assay, Wound healing test and Transwell chamber assay. β-galactosidase staining assay was performed to detect THCA cells senescence. The size and volume of xenotransplanted tumors in nude mice are calculated to asses ZNF24 effect in vivo. Results: Ectopic expression of ZNF24 significantly inhibited the cell viability, colony forming, migration and invasion abilities of THCA cell lines (K1/GLAG-66i and BCPAPi) (P<0.05). ZNF24 induced BCPAPi cells senescence through regulating Wnt signaling pathway. ZNF24 inhibited Wnt signaling pathway activition by competitively binding β-catenin from LEF1/TCF1-β-catenin complex. In nude mice, both Ectopic expression of ZNF24 and 2,4-Da (a potent inhibitor of β-catenin/Tcf-4 [1]) treatment significantly decreased both the size and weight of xenotransplanted tumors when compared with control mice (P<0.05). Conclusion:Both in vitro and in vivo studies showed that ZNF24 could notably inhibited THCA tumorigenesis and invasion by regulating Wnt signaling pathway.